Green Development or Greenwashing? Environmental Histories of Finland - Pál, Viktor; Räsänen, Tuomas (The White Horse Press, 2023)
Finland has often been labelled a 'green superpower', lauded as one of the world's cleanest and greenest countries. Nordic countries in general have tended to be idealised as 'pristine and green', in contrast to the rest of the rapidly contaminating world where the race for markets and profits has enormously accelerated consumption, imposing on the environment an alarming level of extraction and commerce, and a wide array of new and old forms of pollution. Environmental historians, however, can perceive that the reputed 'greenness' of the Nordic countries is partly an illusion. Authors in this volume argue that Finland, similarly to Denmark, Norway and Sweden, has evolved into a green superpower at the cost of considerable environmental problems. Ironically, Finland's current leading position in sustainable development has been built on the heavy use of natural resources and by sacrificing ecosystem health. This volume thus seeks to acquaint the reader with many stories of long-lasting negative environmental impacts in and around Finland: old-growth forests have been replaced by intensive forest farming for lumber and pulp industries; most wetlands have been drained for agriculture, forest cultivation and peat extraction; wild animal populations have been decimated; and Finland today is confined to the south and west by arguably the most polluted sea in the world.There are lessons for the future to be learnt from Finland's tendency to rest on the laurels of a positive environmental reputation built at least in part on myth. In the twenty-first century, the world badly needs less greenwashing and a truer commitment to green-ness.